PAC1 receptor agonist maxadilan alleviates corneal inflammation in a murine model of LPS-induced ocular inflammation - Andras Dobos; Balazs Meresz; Inez Bosnyak; Dorottya Molitor; Bela Kocsis; Edina Szabo; Dora Reglodi; Ildiko Vajda; Tamas Atlasz; Alexandra Vaczy (PLoS ONE, 2026)
Ocular inflammation is a leading cause of visual impairment and blindness worldwide. Systemic bacterial infections can spread hematogenously, resulting in endogenous endophthalmitis. These infections present significant diagnostic and therapeutic challenges due to their systemic origin and involvement of multiple ocular structures such as the retina and cornea. Pituitary adenylate cyclase-activating polypeptide (PACAP), acting through its selective receptor PAC1, exerts potent anti-inflammatory, anti-edema, and regenerative effects in various ocular conditions. This study aimed to assess the protective role of maxadilan, a selective PAC1 receptor agonist, in reducing corneal inflammation in a mouse model of lipopolysaccharide (LPS) -induced ocular inflammation. Mice received systemic LPS injections followed by intravitreal administration of maxadilan. Animals were monitored in vivo using optical coherence tomography (OCT) and tonometry. Post-mortem analyses included evaluation of cytokine expression profiles and routine corneal histological assessment. OCT revealed significantly reduced corneal edema and improved tissue structure with maxadilan administration. Additionally, maxadilan lowered intraocular pressure and reduced inflammatory cell infiltration into the aqueous humor. Cytokine profiling showed decreased expression of critical pro-inflammatory mediators such as GM-CSF, IL-6, MIP-1a, TNF-a, and TREM-1 in the maxadilan-treated group. Histological analyses confirmed that maxadilan preserved normal corneal architecture and effectively prevented pathological keratinization compared to untreated controls. These findings suggest that PAC1 receptor activation has therapeutic potential for controlling inflammation and maintaining corneal health in ocular inflammation.